Development and Validation of Modern UHPLC-DAD Analytical Method for Simultaneous Determination of Repaglinide and Metformin in Pharmaceutical Dosage Forms - Patel, Viralkumar; Pandya, Chintan; Pandya, Aditee; Patel, Zalak; Patel, Dharmesh (Asian Journal of Chemistry, 2020)
For the simultaneous determination of repaglinide and metformin hydrochloride in bulk, an effective and simple UHPLC method was developed and validated and applied to marketed repaglinide and metformin products. The mobile phase used for chromatographic runs consisted of 30 mM phosphate buffer (pH 3.7) and acetonitrile (20:80, v/v) separation was implemented using isocratic mode on an Agilent Zorbax Eclipse Plus C18 (150 × 4.6 mm, 5 μm) column. Drug peaks were well separated and a 232 nm DAD detector observed them. The method was linear for repaglinide and metformin at the concentration range of 20-100 μg/mL, respectively. The method has been validated with respect to system suitability, specificity, accuracy, precision, robustness and ruggedness according to ICH guidelines. Repaglinide and metformin forced degradation studies were conducted for under acidic, base, neutral (peroxide), thermal and photo conditions.